PERILAKU BULLYING PADA SISWA PENDIDIKAN DASAR: FAKTOR PEMICU, DAMPAK, DAN SOLUSI - Akhmad Aji Pradana; Anggita, Andien Frida; Salsabila, Nada Syarifa; Febriyanti, Siska Cahya (PREMIERE : Journal of Islamic Elementary Education, 2025)
Bullying in the school environment is always a serious and urgent issue that must be addressed immediately because of its dangerous and far-reaching impacts. This study investigates bullying cases at MI Al-Musthofawiyah Palang Tuban. It focuses on data from students, teachers, and homeroom teachers. Information was collected through in-depth interviews and observations. The data analysis technique used in this study was the interactive analysis model by Miles & Huberman. This model involves data reduction, display, conclusion, and verification. This article explains the results of the study in more detail. The results include the forms of bullying, its causes, its impacts, ways to prevent it, and solutions for bullying cases at MI Al-Musthofawiyah Palang. Research like this needs to be done again, but on a larger scale. For example, we need to look at different types of students' backgrounds, genders, and educational levels. Also, we need to identify more cases of cyberbullying at the elementary education level. It's also very important for psychologists, health professionals, and the government to work together. The role of religious leaders and the use of social media in the digital age are also highly recommended to prevent bullying cases.